Pathogen Reduction Technologies and Their Impact on Metabolic and Functional Properties of Treated Platelet Concentrates: A Systematic Review - Tsalas, Stavros; Petrou, Eleni; Tsantes, Andreas G.; Sokou, Rozeta; Loukopoulou, Electra; Houhoula, Dimitra; Mantzios, Petros G.; Kriebardis, Anastasios G.; Tsantes, Argirios E. (Seminars in Thrombosis and Hemostasis, 2022)
Pathogen reduction technologies (PRTs) such as Mirasol and Intercept were developed to eliminate transfusion-transmitted infections. The impact of PRTs on platelet function during the storage period, their effect on platelet storage lesions, and the optimal storage duration following PRTs have not been clearly defined. The aim of this study was to systematically review the existing literature and investigate the impact of PRTs on functional alterations of PRT-treated platelets during the storage period. The authors identified 68 studies suitable to be included in this review. Despite the high heterogeneity in the literature, the results of the published studies indicate that PRTs may increase platelet metabolic activity, accelerate cell apoptosis, and enhance platelet activation, which can subsequently lead to a late exhaustion of activation potential and reduced aggregation response. However, these effects have a minor impact on platelet function during the early storage period and become more prominent beyond the fifth day of the storage period. Large in vivo trials are required to evaluate the effectiveness of PRT-treated platelets during the storage period and investigate whether their storage can be safely extended to more than 5 days, and up to the traditional 7-day storage period.
Keywords: pathogen reduction technologies; pathogen inactivated platelets; platelet storage lesion; platelet function